The World Federation of Societies of Biological Psychiatry (WFSBP) Guidelines for the Biological Treatment of Bipolar Disorders: Update 2010 on the treatment of acute bipolar depression. - Grunze, H; Vieta, E; Goodwin, G; Bowden, C; Licht, R; Möller, H; Kasper, S (2010)
OBJECTIVES: These guidelines are based on a first edition that was published in 2002, and have been edited and updated with the available scientific evidence until September 2009. Their purpose is to supply a systematic overview of all scientific evidence pertaining to the treatment of acute bipolar depression in adults. METHODS: The data used for these guidelines have been extracted from a MEDLINE and EMBASE search, from the clinical trial database clinicaltrials.gov, from recent proceedings of key conferences, and from various national and international treatment guidelines. Their scientific rigor was categorised into six levels of evidence (A-F). As these guidelines are intended for clinical use, the scientific evidence was finally assigned different grades of recommendation to ensure practicability. RESULTS: We identified 10 pharmacological monotherapies or combination treatments with at least limited positive evidence for efficacy in bipolar depression, several of them still experimental and backed up only by a single study. Only one medication was considered to be sufficiently studied to merit full positive evidence. CONCLUSIONS: Although major advances have been made since the first edition of this guideline in 2002, there are many areas which still need more intense research to optimize treatment. The majority of treatment recommendations is still based on limited data and leaves considerable areas of uncertainty.